PERFORMATIVE STORYTELLING AND PUBLIC HEALTH: MAPPING PATENT REGIME DISCOURSES THROUGH VISUAL CULTURE - Mehra, Swati; Sharma, Arun; Bhadauria, Sanjiv Singh; Choudhary, Saroj; Gupta, Ishu; Sharma, Vidyottama (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Visual storytelling is becoming an essential part of public health communication as it helps to transform the complicated policy structures into the simple stories that other audiences can readily understand. The legal and economic frameworks that signify the pharmaceutical patent regimes of medicines, vaccines, and medical technologies are sometimes challenging to understand by ordinary people. Posters, campaign graphics, advocacy images, and digital media material as a form of visual culture are one of the most important tools to influence the perception of the population regarding the intellectual property policies and health care access. The study examines the role of performative storytelling in visual culture to create discourses around patent regimes in areas of public health. Analyses of visual cultural analytics and discourse mapping analyses of a curated collection of visual communication materials of governmental agencies, international bodies, pharmaceutical campaigns, and advocacy organizations were conducted. The analysis reveals the patterns of prevalent storytelling trends based on innovation narratives and accessibility narratives. Visionaries focused on innovation will often prioritize science and technological improvement and accessibility stories will focus on humanitarian issues regarding the accessibility of medicine and fairness in healthcare in the world. The analysis of audience engagement proves that empathy-driven storytelling produces the most interaction levels on the digital media platforms. The results explain the use of visual storytelling as a simplification tool to complex health policy discussions and how it can impact the knowledge of pharmaceutical patent regimes to the general population. Combining the study of visual cultural analytics and the study of social forces on a population health policy can give a new interdisciplinary approach to studying how visual storytelling influences societal discourse, relating to healthcare governance.